Late Quaternary glacial history of Khentey Mountains, Central Mongolia - Khandsuren, Purevmaa; Seong, Yeong Bae; Oh, Jeong Sik; Rhee, Hyun Hee; Sandag, Khadbaatar; Yu, Byung Yong (WILEY, 2019)
Mongolian glaciers have been the subject of relatively little research, resulting in less geochronological constraint thanother parts of Central Asia. The Khentey Mountains (latitude 47-51 degrees N, longitude 105-112 degrees E) are a typical landlocked mountain range exhibiting clear geomorphic evidence of late Quaternary glaciation. Yet, compared to western parts of Mongolia such as the Mongolian Altay, Gobi Altay, Khangay, and Khovsgol, glacial history of the Khentey Mountains is poorly understood. To address this, and permit comparison of the Khentey glacier-climate record with other alpine regions in Mongolia, we performed geomorphological mapping and cosmogenic Be-10 surface-exposure dating in two glaciated regions of the Khentey Mountains: Yestii and Khagiin Khar. Specifically, we measured Be-10 in 34 samples collected from five moraine sequences, which, together with morphostratigraphy, correspond to four main glacial stages: (i) The M-y1 terminal moraine sequence for Yestii (21.0 +/- 4.9 ka) and the M-k1 moraine for Khagiin Khar (19.6 +/- 2.6 ka), both of which represent the Last Glacial Maximum; (ii) the Lateglacial M-k2 moraine, dated to 16.0 +/- 3.5 ka; (iii) the M-k3 moraine, dated to either 17.6 +/- 7.0 ka (Lateglacial) or 12.1 +/- 1.1 ka (Younger Dryas); and (iv) the currently undated M-k4 moraine (similar to 2200m a.s.l.), to which we assign a Holocene age. Our results suggest that the timing of maximum glacier extent in Mongolia was regionally variable. In the Khentey Mountains, maximum glaciation occurred during Marine Isotope Stage (MIS) 2, whereas the maximum occurred during MIS 3 in Khangay and Khovsgol and during MIS 4 in the Altay. The MIS 2 glacial maximum in the Khentey Mountains coincided with the global sea level minimum during the Last Glacial Maximum, and was followed by at least three glacial re-advances during the Lateglacial to possibly the Holocene.
Keywords: LATE PLEISTOCENE GLACIATIONS; EQUILIBRIUM-LINE ALTITUDES; HOLOCENE CLIMATE EVOLUTION; NORTH CENTRAL MONGOLIA; WINTER MONSOON; GLOBAL CLIMATE; DIATOM RECORDS; EROSION RATES; NUUR BASIN; UGII NUUR